HUBUNGAN ANTARA KEDISIPLINAN DALAM BELAJAR DENGAN HASIL BELAJAR SISWA KELAS V DI MI AL-FALAH CIBINONG KABUPATEN BOGOR - Dhiya Rahma Rauqillah; Chodidjah Makarim; Mukhtar Mukhtar (Attadib: Journal of Elementary Education, 2018)
In the process of teaching and learning, discipline can be a preventive tool to prevent and keep things that can disrupt and hinder the learning process to get a good learning results. The issue of discipline is one of the issues facing schools. because the discipline in learning is an attitude that demonstrates a willingness to perform or comply with the conditions, and code of conduct which is enforced at the school. The purpose of this research is to know the discipline students, knowing the results of student learning, knowing attitude of disciplined learning students, aware of the relationship between student learning outcomes by discipline, know the benefits of discipline in learning against the student learning outcomes, knowing the factors that influence student learning, discipline and knowing the factors that influence student learning outcomes. This research uses research methods korelasional according to Nana Syaodih that korelasional research aims to know the relationship between variables X and Y variables. I.e. by means of dissemination of the results of the study and the now UTS students. Research results are now shown by the discipline of 35 respondents there are 14 students (40%) belongs to the category and the results of the study of the value of the UTS there are 10 students (42.86%) belong to the category of good results with correlation is 0.047 then It can be concluded that there is a relationship between a discipline in learning with student learning outcomes.